Buku Ilustrasi Mengenai Pemenuhan Gizi Melalui Bahan Pangan Alternatif Untuk Kalangan Usia Produktif - Nur Azizah Susetyaningsih; Mahimma Romadhona; Masnuna (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2022)
Cases of imbalances in nutritional consumption among children and adolescents in their infancy, which have an impact on adulthood and the elderly are still widely found. The causative factor is generally due to lack of knowledge about the type of food that can meet the nutrition of each meal. Food in the form of conventional types of vegetables have been widely recognized, but the fact that there are alternatives known as indigenous vegetables are still rarely known. Therefore, this paper will discuss the creation of an illustration book concerning the fulfillment of nutrition through alternative food in favor to the productive age group as an educational medium for diversifying alternative food in Indonesia, especially for people in the age range of 18 to 26 years. The methods used are quantitative and qualitative descriptive, with data sources collected through respondents within the range of segmentation targets, as well as through in-depth interviews about nutrition that affects health. The study of scientific literature related to nutritional content and alternative food is also carried out to deepen information for the creation of illustration books.